2010
DOI: 10.1103/physrevb.81.235217
|View full text |Cite
|
Sign up to set email alerts
|

Isotopic fingerprints of Pt-containing luminescence centers in highly enrichedS28i

Abstract: Recently we have shown that the reduction in the photoluminescence linewidth of many deep luminescence centers in highly enriched 28 Si results in well-resolved isotopic fingerprints. This allows for a better characterization of a defect center, as not only the involvement of a specific element but also the number of atoms of that element within the complex can be determined. Surprisingly, we have found that many well-known luminescence centers have a different composition than originally supposed. In addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 12 publications
1
9
0
Order By: Relevance
“…Indirect-gap semiconductors are more common, but their scintillation is slow and inefficient without doping. However, luminescence has been reported from Si [66,67] and Ge [68] at cryogenic temperatures (Table I suitable dopants to achieve high radiative efficiency. We show results for Ge and Si below since they are potential scintillators and are also used in current experiments sensitive to an ionization signal, like SuperCDMS and DAMIC.…”
Section: Scintillating Targetsmentioning
confidence: 99%
“…Indirect-gap semiconductors are more common, but their scintillation is slow and inefficient without doping. However, luminescence has been reported from Si [66,67] and Ge [68] at cryogenic temperatures (Table I suitable dopants to achieve high radiative efficiency. We show results for Ge and Si below since they are potential scintillators and are also used in current experiments sensitive to an ionization signal, like SuperCDMS and DAMIC.…”
Section: Scintillating Targetsmentioning
confidence: 99%
“…Stegner et al also identified an entire family of apparently similar PL centers including various combinations of Cu, Ag, Au, Li, and other metallic impurities, all of them containing "at least four," and in a few cases, "at least five," metallic impurities. 25,26 No defect containing two or three metallic impurities is visible in the PL spectra.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the decay to 197 Au and 197 Pt allowed for more multi-atom centres to be identified. These results are summarized in numerous papers [60,61] and have opened a considerable challenge to existing theory which remains open. Since this work, 28 Si has found a unique application in the field of quantum computing and is one of the most promising materials for the realization of next generation devices.…”
Section: Photoluminescence (Pl) Spectroscopymentioning
confidence: 99%
“…11 Be(t 1/2 =14 s); 27 Mg (9.5 min), 56 Mn (2.6 h) and 61 Co (1.6 h). A full description of the new chamber can be found in a recent review article [69].…”
Section: Emission Channellingmentioning
confidence: 99%